The state as an eager shareholder - Hadrien Coutant; Scott Viallet-Thévenin (Revue de la Régulation)
This article discusses the way financialization impacts state ownership of capital. We show that financialization can occur in state-owned enterprises following a specific pattern that differs from the common narrative about the diffusion of shareholder value. An exploration of the transformation of the governance of SOEs in France shows that the conception of control of firms implemented by the state has changed dramatically since the 1980s. The creation of the Ministry of Finance’s Agence des participations de l’État can be viewed as a turning point in these transformations. To illustrate these changes, we focus on the financialization process of SOEs in two case studies from the energy and aeronautics industries. Our analysis confirms the specific role of the French state in organizing the economy while opposing the assumption that this supposedly limits the financialization of firms.capitalism, financialization, economic sociology, France, corporate governance, organizational change